1999
DOI: 10.1128/jb.181.21.6600-6606.1999
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Cell Wall Component Teichuronopeptide to pH Homeostasis and Alkaliphily in the Alkaliphile Bacillus lentus C-125

Abstract: A teichuronopeptide (TUP) is one of major structural components of the cell wall of the facultative alkaliphilic strain Bacillus lentus C-125. A mutant defective in TUP synthesis grows slowly at alkaline pH. An upper limit of pH for growth of the mutant was 10.4, while that of the parental strain C-125 was 10.8. GenetupA, directing synthesis of TUP, was cloned from C-125 chromosomal DNA. The primary translation product of this gene is likely a cytoplasmic protein (57.3 kDa) consisting of 489 amino acid residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…There is strong evidence that monovalent cation/proton antiporters are essential for maintaining a neutral cytoplasmic pH and, therefore, for growth under alkaline conditions (Krulwich, 1995). In addition, acidic cell wall polymers contribute to pH homeostasis (Aono et al, 1999). Again, how facultative alkaliphilic bacilli can cope with a sudden alkaline shock has never been examined in detail on a transcriptional level.…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that monovalent cation/proton antiporters are essential for maintaining a neutral cytoplasmic pH and, therefore, for growth under alkaline conditions (Krulwich, 1995). In addition, acidic cell wall polymers contribute to pH homeostasis (Aono et al, 1999). Again, how facultative alkaliphilic bacilli can cope with a sudden alkaline shock has never been examined in detail on a transcriptional level.…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for the survival of these indigenous cement isolates at high pH might be their highly alkaline habitat. Reportedly, certain structural components of the cell wall of some alkalophiles, such as teichuronopeptide, may contribute to pH homeostasis at alkaline pH and aid bacteria to survive in alkaline environments [6]. Owing to the ability to tolerate high pH, CT5 enhanced the compressive strength of cement mortar cubes significantly and is regarded as a microbial concrete producer [2].…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of B. cereus ATCC 10702 at pH 11, results also suggested that the alkaline buffering capacity for both Bacillus DL5 and B. cereus ATCC 10702 may possibly be cell wallassociated. Reportedly, certain structural components of the cell wall of some alkalophiles, such as teichuronopeptide, may contribute to pH homeostasis at alkaline pH and aid bacteria to survive in alkaline environments (Aono et al 1999). Similar types of cell wall components may be present in Bacillus DL5 and B. cereus ATCC 10702 cells aiding in survival at alkaline pHs, although they were shown not to be alkalophiles.…”
Section: Discussionmentioning
confidence: 99%